PENGEMBANGAN TAMAN WANASUTAN ASRI DUSUN SEMBEGO MAGUWOHARJO MELALUI TEKNOLOGI DIGITAL UNTUK EDUKASI DAN REKREASI - Dini Al Islami, Rizki Nur'Allam (UIN Sunan Kalijaga, 2025)
The development of community-based tourism villages in Sembego Village, Maguwoharjo, Sleman Regency, is a strategic effort to optimize local potential while improving the welfare of the community in a sustainable manner. A key focus is to enhance the community's digital literacy through socialization, education programs, and the creation of a village website as an information and promotional tool. This website is designed to provide complete information about Taman Wanasutan Asri Tourism Village, including tourist attractions, facilities, and events, while expanding marketing networks through digital platforms. The implementation method includes identifying environmental issues, selecting priority solutions, and involving the community in every stage. This program is expected to have a positive impact by improving the community's digital skills, strengthening their understanding of community-based tourism, and creating an inclusive and sustainable tourism ecosystem. With this development, Sembego Village is expected to become a competitive tourism destination that contributes positively to the local economy and serves as an inspiring model for other tourism villages in Indonesia.